Indonesia’s Military Modernization and Regional Diplomatic Influence, 2005-2024 - Satryo Pringgo Sejati; Try Danuwijaya (CV Putra Publisher, 2026)
This article examines the relationship between Indonesia’s military modernization and its regional diplomatic influence in Southeast Asia from 2005 to 2024. The study aims to empirically assess whether sustained increases in defence expenditure contribute to strengthening Indonesia’s diplomatic influence within ASEAN’s cooperative security framework. Grounded in a positivist approach and informed by realism and power transition theory, the study assumes that material capability can support diplomatic influence, while recognizing that its effects are mediated by institutional and normative factors, including leadership in regional forums and adherence to ASEAN consensus-based norms. The study employs a quantitative longitudinal design using annual data on defence expenditure, diplomatic influence, and macroeconomic indicators. Diplomatic influence is operationalized using the “diplomatic influence” component of the Asia Power Index, which captures a country’s ability to shape regional outcomes through diplomatic networks and institutional engagement. The analysis combines Pearson correlation, scatter plot visualization, and multiple linear regression. The findings show that while Indonesia’s military expenditure increased significantly over time (r = 0.929; p < 0.001), its relationship with diplomatic influence is weak and statistically insignificant (r = 0.160; p > 0.05), and remains insignificant in the regression model (β = −0.004; R² = 0.209). These results indicate that military modernization does not independently enhance diplomatic influence when tested alongside other variables. Instead, Indonesia’s regional influence is more strongly associated with institutional engagement, multilateral diplomacy, and leadership within ASEAN mechanisms. This study contributes to the literature by providing longitudinal quantitative evidence, which remains limited in existing research on defense diplomacy in ASEAN that is largely qualitative or descriptive. The findings suggest that military modernization is a necessary but insufficient condition for enhancing regional influence, highlighting the importance of integrating material capability with institutional and cooperative diplomatic strategies.